We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
695
3
avatar

does √x-y = √x-√y

 Jan 12, 2016

Best Answer 

 #2
avatar+104855 
+5

√x-y = √x-√y   (???)    square both sides

 

x - y = x - 2√[x *y]  + y    subtract x from both sides  and rearrange

 

2√[x *y]  = 2y        divide both sides by 2

 

√[x * y]  = y

 

√x * √y  = y

 

√x * √y  - y  =  0        factor

 

√y [ √x  - √y]  = 0

 

So either    √y  = 0      or    √x  = √y

 

So....the original equation is true only when x = y   or    y = 0

 

 

cool cool cool

 Jan 12, 2016
 #1
avatar+1832 
+5

NOOOOOO 

You can't 

it works for multiplcation or division 

 Jan 12, 2016
 #2
avatar+104855 
+5
Best Answer

√x-y = √x-√y   (???)    square both sides

 

x - y = x - 2√[x *y]  + y    subtract x from both sides  and rearrange

 

2√[x *y]  = 2y        divide both sides by 2

 

√[x * y]  = y

 

√x * √y  = y

 

√x * √y  - y  =  0        factor

 

√y [ √x  - √y]  = 0

 

So either    √y  = 0      or    √x  = √y

 

So....the original equation is true only when x = y   or    y = 0

 

 

cool cool cool

CPhill Jan 12, 2016
 #3
avatar+1904 
+5

If you mean \(\sqrt{x-y}\), you cannot seperate \(x\) and \(y\) into \(\sqrt{x}-\sqrt{y}\). If \(x\) and \(y\) was \(\sqrt{x\times y}\), then you can seperate \(x\) and \(y\) into \(\sqrt{x}\times\sqrt{y}\).  If \(x\) and \(y\) was \(\sqrt\frac{{x}}{y}\), then you an seperate \(x\) and \(y\) into \(\frac{{\sqrt x}}{\sqrt y}\).  If you mean \(\sqrt{x}-y\), you cannot add a \(\sqrt{}\) to y, that would change the problem entirely.

 

Example:

 

Let \(x=3\) and let \(y=2\)

 

\(\sqrt{x-y}\)

 

\(\sqrt{3-2}\)

 

\(\sqrt{1}\)

 

\(1\)

 

The answer is \(1\)

 

Now lets do \(\sqrt{x}-\sqrt{y}\)

 

Let \(x=3\) and let \(y=2\)

 

\(\sqrt{x}-\sqrt{y}\)

 

\(\sqrt{3}-\sqrt{2}\)

 

\(1.7320508075688773...-1.414213562373095...\)

 

\(0.3178372451957823...\)

 

The answer is \(0.3178372451957823...\)

 

\(1\) and \(0.3178372451957823...\) are not the same answer.

 

Now lets do \(\sqrt{x\times y}\)

 

Let \(x=3\) and let \(y=2\)

 

\(\sqrt{x\times y}\)

 

\(\sqrt{3\times 2}\)

 

\(\sqrt{6}\)

 

\(2.4494897427831781...\)

 

The answer is \(2.4494897427831781...\)

 

Now lets do \(\sqrt{x}\times\sqrt{y}\)

 

Let \(x=3\) and let \(y=2\)

 

\(\sqrt{x}\times\sqrt{y}\)

 

\(\sqrt{3}\times\sqrt{2}\)

 

\(1.7320508075688773... \times 1.414213562373095...\)

 

\(2.4494897427831781...\)

 

The answer is \(2.4494897427831781...\)

 

\(2.4494897427831781...\) and \(2.4494897427831781...\) are the same answer.

 

Now lets do \(\sqrt\frac{{x}}{y}\)

 

Let \(x=3\) and let \(y=2\)

 

\(\sqrt\frac{{x}}{y}\)

 

\(\sqrt\frac{{3}}{2}\)

 

\(1.224744871391589...\)

 

The answer is \(1.224744871391589...\)

 

Now lets do \(\frac{{\sqrt x}}{\sqrt y}\)

 

Let \(x=3\) and let \(y=2\)

 

\(\frac{{\sqrt x}}{\sqrt y}\)

 

\(\frac{{\sqrt 3}}{\sqrt 2}\)

 

\(\frac{1.7320508075688773...}{1.414213562373095...}\)

 

\(1.224744871391589...\)

 

The answer is \(1.224744871391589...\)

 

\(1.224744871391589...\) and \(1.224744871391589...\) is the same answer

 

Now lets do \(\sqrt{x}-y\)

 

Let \(x=3\) and let \(y=2\)

 

\(\sqrt{x}-y\)

 

\(\sqrt{3}-2\)

 

\(1.7320508075688773...-2\)

 

\(-0.2679491924311227...\)

 

The answer is \(-0.2679491924311227...\)

 

Now let do \(\sqrt{x}-\sqrt y\)

 

Let \(x=3\) and let \(y=2\)

 

\(\sqrt{x}-\sqrt y\)

 

\(\sqrt{3}-\sqrt 2\)

 

\(1.7320508075688773...-1.414213562373095...\)

 

\(0.3178372451957823...\)

 

The answer is \(0.3178372451957823...\)

 

\(-0.2679491924311227...\) and \(0.3178372451957823...\) are not the same answer

 

Hope this helps

 Jan 12, 2016

21 Online Users

avatar
avatar
avatar